Analisis Kandungan Boraks dan Formalin pada Produk Olahan Daging yang dijual oleh UMKM di Kota Bandung - Alifia, Nabila Nissa; Marlina, Eulis Tanti; Utama, Dicky Tri (Unpad Press, 2023)
Beef meatballs and chicken nuggets are popular processed meat products that are in great demand. Currently, many micro, small, and medium enterprises (MSME) produce beef meatballs and chicken nuggets and then sell them through online e-commerce. Bandung City is one of the cities with 121,530 (26.17%) out of 464,346 MSMEs in food sector. This study aims to evaluate the food safety of beef meatballs and chicken nuggets produced by MSMEs in Bandung City with online sales to various cities in Indonesia. The content of sodium borate (borax) and formaldehyde, which in many cases are added to replace legal food additives to beef meatballs and chicken nuggets. The research was conducted descriptively with qualitative and quantitative methods. The number of samples was 20 products (14 beef meatball products and 6 chicken nugget products) from 20 different MSMEs in Bandung City. The turmeric paper method was used for detecting borax qualitatively, while the KMnO4 reagent method was used for detecting formaldehyde. Positive results were quantitatively tested using spectro-photometer. The results showed that no samples contained borax, but 7 samples (35%) contained formaldehyde, which ranged from 4.16-12.44 ppm. The level of formaldehyde in beef meatballs sold by several MSMEs in Bandung City has violated the rules set in Indonesia.